DESIGNING URBAN GREEN INFRASTRUCTURE IN JAKARTA: AN URBAN FORESTRY APPROACH TO MITIGATE THE URBAN HEAT ISLAND EFFECT AND ENHANCE BIODIVERSITY - Darmawan Listya Cahya; Epi Taua; Loma Latu (Yayasan Adra Karima Hubbi, 2025)
Jakarta faces a severe Urban Heat Island (UHI) crisis and biodiversity loss, challenges compounded by current greening policies that prioritize aesthetics over functional ecological design. This study addresses the lack of a systematic Urban Forestry Design Methodology tailored for hyper-dense tropical megacities. The primary objective was the development and validation of the Dual-Benefit Urban Forestry (DBUF) Model, a prescriptive, GIS-based tool that simultaneously optimizes micro-climate mitigation and native biodiversity enhancement. The methodology employed a geospatial and computational modeling design, utilizing Landsat imagery to map UHI intensity and correlating it with existing UGI features for diagnostic analysis. The DBUF Model was then simulated and assessed in pilot urban zones. Results demonstrated the DBUF Model’s superior performance: optimized layouts achieved a predicted 3.5^°C reduction in Land Surface Temperature, significantly outperforming existing UGI’s 0.8^°C reduction, while concurrently predicting a 60% increase in native bird species richness. The study concludes that the DBUF Model provides the necessary scientifically rigorous framework to shift policy from opportunistic landscaping to performance-based urban forestry, ensuring maximum functional ecological return from limited urban space.